Chemical constituents of Aglaia Lanuginose. King / Fadzly Adzhar bin Kamarulzaman - Kamarulzaman, Fadzly Adzhar (2010)
Aglaia is a small genus of trees that belong to the family Meliaceae. They are widely distributed in India, Malay Peninsula and throughout Indomalesia. The chemistry of Aglaia has been extensively investigated and most of the researches done on these plants focused on their effect as insecticides, antifeedant, growth inhibitors, cytotoxicity and others. The dichloromethane extract from the bark of Aglaia lanuginose were studied. The chromatographic separation on both of the extracts gave ten compounds. The compounds isolated were identified as eichlerialactone 102, methyl eichlerianate 103, cabraleone 104, ocotillone 105, 4-hydroxycinnamyl acetate 106, cabralealactone 107, eichlerianic acid 108, shoreic acid 109 and the sterols, sitosterol 110 and stigmasterol 111. 4- Hydroxycinnamyl acetate 106 is reported for the first time in Meliaceae family.